92.5k views
0 votes
6≥−6(a+2) solve and find the awnser

User Boog
by
5.2k points

2 Answers

5 votes

Answer:

-3<=a

Explanation:

1. Get the -6 away, so multiply everything by -6. 6*-6 >= -6*-6(a+2)

2. This becomes -1 <= a+2 Since if you multiply or divide anything by a negative number, you have to reverse the inequality sign.

3. Subtract 2 to get a by itself -1-2 >= a

4. This becomes -3 >= a which is the right answer.

(Just so you know >= and <= means less than or equal to and more than or equal to.)

User Helen Hakobyan
by
5.7k points
0 votes

Answer:


- 3 \geqslant a

Explanation:


6 \geqslant - 6(a + 2)

distribute -6 inside the parentheses


6 \geqslant - 6a - 12

add 12 to both sides


18 \geqslant - 6a

divide by -6 to isolate the variable


- 3 \geqslant a

User AlBlue
by
5.1k points